Caveolin and oxidative stress in cardiac pathology - Zadorozny, Lauren; Du, Jiayue; Supanekar, Neil; Annamalai, Karthik; Yu, Qing; Wang, Meijing (Frontiers in Physiology, 2025)
Caveolins interact with signaling molecules within caveolae and subcellular membranes. Dysregulation of caveolin function and protein abundance contributes to cardiac pathophysiological processes, driving the development and progression of heart disease. Reactive oxygen species (ROS) play a critical role in maintaining cellular homeostasis and are key contributors to the pathophysiological mechanisms of cardiovascular disorders. Caveolins have been shown to modulate oxidative stress and regulate redox homeostasis. However, the specific roles of caveolins, particularly caveolin-1 and caveolin-3, in regulating ROS production during cardiac pathology remain unclear. This mini-review article highlights the correlation between caveolins and oxidative stress in maintaining cardiovascular health and modulating cardiac diseases, specifically in myocardial ischemia, heart failure, diabetes-induced metabolic cardiomyopathy, and septic cardiomyopathy. A deeper understanding of caveolin-mediated mechanisms may pave the way for innovative therapeutic approaches to treat cardiovascular diseases.